Unsupervised machine learning revealed a correlation between low-dose statins and favorable outcomes in ICH patients - Cui, Chaohua; Guan, Haoye; Long, Tonghua; Liang, Yuru (Frontiers in Neurology, 2025)
BackgroundStatins were effective in preventing ischemic stroke in patients with intracerebral hemorrhage (ICH). Statins administered at normal doses may contribute to hematoma expansion. We employed unsupervised machine learning methods and found that low-dose statins improve the prognosis of ICH.MethodsWe employed unsupervised machine learning techniques to analyze unidentified factors within a retrospective cohort related to the prognosis of ICH. In our prospective cohort study, data were gathered from ICH patients over a three-year period. Outcomes included mortality, cerebrovascular events within 3 years, unfavorable functional outcomes at 3 months, and hematoma expansion during hospitalization.ResultsThe heatmap illustrated distinct statin effect trajectories, emphasizing the substantial impact of low-dose statins on prognosis. The low-dose statin group exhibited reduced mortality (p = 0.001), a decreased rate of unfavorable functional outcomes (p < 0.001), and fewer cerebrovascular events (p < 0.001). Both groups demonstrated a comparable rate of hematoma expansion (p = 0.735). In multivariable Cox regression analyses, low-dose statins were associated with reduced mortality (RR = 0.505, p = 0.022) and decreased ischemic stroke occurrence (RR = 0.354, p < 0.001). Additionally, low-dose statins were linked to better functional outcomes (OR = 0.594, p < 0.001) but showed no significant association with hematoma expansion (OR = 1.056, p = 0.735).ConclusionUnsupervised machine learning revealed a correlation between low-dose statins and patient prognosis. Subsequent analyses and validation indicated that for patients with intracerebral hemorrhage (ICH) in the cerebral hemisphere, early administration of low-dose hydrophilic statins is associated with reduced mortality, and statins are associated with a reduced rate of ischemic stroke occurrence. For all ICH patients, low-dose statins are associated with a lower rate of unfavorable functional outcomes but show no significant association with hematoma expansion.